Pesan dan Kontroversi Sedekah oleh Ustaz Yusuf Mansur dalam Channel Youtube JIATV - Siregar, Yudi Andhika; Sikumbang, Ahmad Tamrin; Muktarruddin, Muktarruddin (Darul Yasin Al Sys, 2023)
In general, the aim is to understand the messages and controversies about Ustaz Yusuf Mansur's almsgiving on the JIATV YouTube channel so that the public knows what almsgiving is right and what is wrong and so that the public knows what the initial basis for almsgiving itself is. And what are the hadiths and verses of the Koran that explain the meaning alms. This study uses a qualitative method. The researcher uses the Roland Barthes model of semiotic methods. Roland Barthes' Semiotic Analysis examines signs and how they work. This idea is based on Saussure's thoughts regarding signs which he divided into signifiers and signifieds, where Barthes' analysis is divided into several stages of analysis, namely denotation, connotation and myth. . The results of my research are: firstly, the dominance of the da'wah message conveyed by Ustad Yusuf Mansur is more inclined towards the recommendation of almsgiving. Almsgiving is an obligatory thing, almsgiving is a pious practice that is recommended. This is indicated through Yusuf Mansur's journey in interpreting almsgiving itself. secondly, the controversy over the message of alms according to Ustaz Yusuf Mansur is that it tends to be more materialistic in nature, which is merely alms, which means only seeking retribution in the form of money which is doubled, which tends to be forced to give alms by Ustaz Yusuf Mansur.